GE_GERICHTE C/4547/2010 vom 3. November 2014 - GE Cour de justice (2014)
REMBOURSEMENT DE FRAIS(SENS GÉNÉRAL); AVANCE DE FRAIS; DÉCISION SUR FRAIS | CPC.98; CPC.103; CPC.104; CPC.110; CPC.238; CPC.319.B.1; CPC.404.1; CPC.405.1